Determination of Eating Attitude and Mindful Eating Scores of Patients in Turkey - Cebirbay, M. Ali; Kitis, Cağrı (Progress in Nutrition, 2022)
The study aims to evaluate the status of eating attitude and mindful eating of adult patients (n=905) who applied to diet polyclinics in hospitals in Afyonkarahisar, Turkey. The data were collected by face-to-face interviews using a 4-part questionnaire form, including socio-demographic features and nutritional habits, anthropometric measurements, Eating Attitude Test (EAT-40) and Mindful Eating Questionnaire (MEQ-30). Data were analyzed using SPSS 25.0 version. In total, 5.4% of patients had eating disorders; underweight patients were associated significantly with an overall eating disorder (p